Canadian and English students' beliefs about waterpipe smoking: a qualitative study. - Roskin, J; Aveyard, P (2009)
BACKGROUND: Waterpipe smoking is becoming popular among western students. The aim was to understand the appeal to students of this form of smoking when other forms of smoking are becoming less common. METHODS: Waterpipe smokers were identified by snowball sampling and interviewed following a semi-structured schedule in waterpipe cafes and in their homes. Constant comparative analysis was used to derive themes for the analysis. RESULTS: Waterpipe smokers saw smoking as an alternative to more expensive nights out in bars. The appeal was related to the communal activity and the novelty of the experience. Respondents had not thought deeply about the health risks and reasoned that if no warnings about waterpipe smoking were apparent (unlike cigarette smoking) then it was probably safe. These observations were reinforced by observations about the mildness of the smoke, the fruit flavours, and beliefs about the filtering of the water. Waterpipe smokers felt no pressure to stop smoking and therefore had not tried to do so, but felt it might be something they did not continue after university. Waterpipe smoking was not linked in students' minds to other forms of smoking except in one individual who was using waterpipe smoking to help quit cigarettes. CONCLUSION: In the absence of public health information, students have fallen back on superficial experiences to form views that waterpipe smoking is less harmful than other forms of smoking and it is currently much more acceptable in student society than other forms of smoking.